Implementasi Program Pembelajaran Berbasis Budaya Lokal Melalui Hidden Curriculum - Widiatsih, Asri; Triono, Untung; Citra P., Nostalgianti (JOEAI (Journal of Education and Instruction), 2021)
This study aims to describe the implementation of local culture-based learning through the Hidden Curriculum at SMP Negeri 1 Sumberbaru Jember. The approach in this research is qualitative research, with case studies. Meanwhile, the object of this research is SMP Negeri 1 Sumberbaru, Jember Regency. The data collection technique uses observation, interview, and documentation techniques with data analysis using qualitative data analysis procedures consisting of: data condensation, data presentation, and inference/verification. The results showed that the implementation of local culture-based learning programs through a hidden curriculum was carried out by: (1) intracurricular activities, (2) co-curricular and (3) extracurricular activities. Conclusion, Hidden curriculum through intracurricular activities in the form of art and dance subjects. Co-curricular activities can be implemented by integrating them into the learning program, the activities implemented are the habit of coming in the morning, the role of the BK teacher, the celebration of religious holidays and the role of the school committee. The chosen extracurricular activity is dance, which is a characteristic of East Java. Keywords: Hidden Curriculu, Local Culture-based Learning